(untitled) (Research, Society and Development, 2021)
Herbal treatments have gained strength in recent years, mainly for the treatment of obesity, but there is little scientific evidence about them. Thus, the present study aimed to conduct a critical analysis of its commercialization and effectiveness in the treatment of obesity. The research was carried out in manipulation pharmacies and drugstores in the city of Teresina - PI, through an observational analysis, the technical information of the products whose active ingredient is the Grapefruit Citrussinensis (morosil) was analyzed. In addition, a search for articles will also be carried out in the following databases Science Direct, PubMed and MEDLINE. The table below shows the specifications of the morosil formulations sold in pharmacies in Teresina-PI, where they are mostly sold in the presentation of capsules, with the exception of pharmacy C type 2, which also has the sachet presentation. All formulations have a dosage of 500mg, with the exception of Pharmacy E type 1, consequently, all have a dosage once a day, except Pharmacy E type 1 which has a dosage twice a day. All have free sales. Prices between pharmacies range from 188 R to 90 R, with Pharmacy D having the morosil options associated with other components or in isolation. Given the above, it is possible to infer the information contained in the masterful formulations of the products handled are essentially important to ensure good pharmacological adherence, minimize potential adverse effects, ensure safety and efficacy.